Strategi Optimalisasi Marketing Mix 4P untuk Peningkatan Tingkat Hunian Berkelanjutan: Studi Kasus Kost Rahmi Muara Bungo - Wardani, Rahmi; Azra, Tuti; Wimeina, Yudhytia (Universitas Medan Area, 2025)
This study aims to comprehensively analyze the implementation of the 4P Marketing Mix (Product, Price, Place, Promotion) in the Rahmi Muara Bungo boarding house business and to formulate sustainable optimization strategies for increasing its occupancy rate. Employing a qualitative approach with a case study design, primary data were collected through in-depth interviews with the owner/manager and diverse tenants, supplemented by direct observation of facilities and promotional initiatives. The research findings reveal a current marketing focus on providing basic facilities, highlighting the strategic location, and relying on word-of-mouth promotion. In-depth analysis, grounded in Service-Dominant Logic (value creation through service exchange) and the Resource-Based View (strategic role of internal resources), identifies significant opportunities for enhancement across each element of the Marketing Mix. These include upgrading facilities responsive to tenant needs, adjusting pricing structures to be more flexible and value-oriented, actively promoting the advantages of location and accessibility, and developing a comprehensive digital marketing strategy. The study concludes that an integrated and holistic optimization of the 4P Marketing Mix, focusing on enhancing value for tenants and the effective utilization of existing resources, is crucial for achieving a sustainable increase in the occupancy rate and strengthening the competitive position of the Rahmi Muara Bungo boarding house within the local accommodation market.